2012
DOI: 10.1515/1556-3758.1931
|View full text |Cite
|
Sign up to set email alerts
|

Refining of Crude Canola Oil using PSA Ultrafiltration Membrane

Abstract: The aim of this paper was to study the behavior of spiral wound configuration of polysulfone amide (PSA) membrane with 20 kDa molecular weight cut off (MWCO) in pilot-plant scale equipment used for refining micella canola oil under different operating conditions. Refining process parameters including phospholipids (PLs), color and free fatty acids (FFAs) were measured to express retentions (R%) and the permeate flux, membrane fouling and hydraulic resistances were determined to analyze the ultrafiltration proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Rafe et al 73 studied the effect of temperature on PL retention by membranes. Increasing temperature decreased retention; this might be due to the dissolution of the PLs or disruption of the reverse micellar structure.…”
Section: Membrane Degummingmentioning
confidence: 99%
“…Rafe et al 73 studied the effect of temperature on PL retention by membranes. Increasing temperature decreased retention; this might be due to the dissolution of the PLs or disruption of the reverse micellar structure.…”
Section: Membrane Degummingmentioning
confidence: 99%
“…(78,92,93) In a nonpolar environment, such as hexane or oil, phospholipid particles reveal a tendency to form reverse micelles with a mean molecular weight of 20 kDa or more. (94) Such a large molecular weight makes it possible to separate phospholipids from triacylglycerols (of molecular weight of about 0.8 kDa) by the ultrafiltration method using appropriate membranes.…”
Section: Removal Of Phospholipidsmentioning
confidence: 99%
“…To date, a significant limitation for applying this method was the low stability of membranes in organic solvents and a low flow of the permeate. Rafe et al (92) demonstrated that a spiral wound configuration of polysulfone amide (PSA) membrane made it possible to obtain a high degree of phospholipid removal from rapeseed oil -99.6%. Niazmand et al (93) on the other hand, found that the pretreatment of rapeseed oils with sodium dodecyl sulfate (SDS) and ethylenediaminetetraacetic acid (EDTA) before ultrafiltration with the use of polyvinylidene fluoride (PVDF) membrane made it possible to remove 89% of the total phosphorus content.…”
Section: Removal Of Phospholipidsmentioning
confidence: 99%
“…published his patent: Refining Crude Oil by Filtration. Various membrane materials for purifying solvent oils/crude oils have been explored experimentally by different research teams in which they have achieved great success in the purification of the membrane [ 20 ]. So, purification of the membrane is performed by molecular size as well as molecular weight, and membrane materials are divided into organic and inorganic membranes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%